Hydrogen absorption and desorption properties of Li-Mg-Al-Ti-M based lightweight high entropy alloys - Hirotada Hashimoto; Shigehito Isobe; Tatsuya Minami; Kohta Asano; Kouji Sakaki; Naoyuki Hashimoto; Hiroshi Oka (Next Materials)
The hydrogen absorption and desorption properties of the Li-Mg-Al-Ti-V and Li-Mg-Al-Ti-Nb lightweight high entropy alloys (HEAs) synthesized by mechanical alloying were investigated to develop hydrogen storage alloys with high gravimetric capacity. An equiatomic Li20Mg20Al20Ti20V20 consists of two phases; a Ti-V based body-centered cubic (BCC) phase and a Li-Mg based BCC phase. The alloy absorbs hydrogen up to H/M = 0.74 (2.3 wt% H2) at 250 ℃, although the hydrogen absorption and desorption induced phase separation of Mg from the Li-Mg based BCC phase. The hydrogen absorption and desorption properties of each Li8Mg8Al28Ti28V28 and Li8Mg8Al28Ti28Nb28 single BCC phases were also investigated. At room temperature, they absorbed hydrogen up to H/M = 0.43 (1.1 wt% H2) and H/M = 0.68 (1.4 wt% H2), respectively. Unlike Li20Mg20Al20Ti20V20, no clear phase separation was observed in these alloys after hydrogen absorption and desorption.